ANALYSIS OF ARABIC TRANSLATION DIGITAL DICTIONARY APPLICATIONS IN THE ERA OF SOCIETY 5.0 - Aprilia, Risda; Massofia, Fitrah Dinanti; Hasaniyah, Nur (UIN Maulana Malik Ibrahim Malang, 2024)
Translation is needed as a tool to make it easier to understand a language called a dictionary. At present we can find that dictionaries are not only in printed form, but along with the sophistication of technology, digital dictionary innovations have emerged. The digital dictionary plays an important role in the process of someone understanding a language from its speakers, and as a technological tool in the form of an application and has many roles in the learning process. This research is included in descriptive research with a qualitative approach, and using library research techniques is the step of the researcher in collecting data on the digital Arabic dictionary application. While data analysis is a narrative study on